Advances in aptasensors for the detection of food contaminants. Issue 13 (6th June 2016) - Duan, Nuo; Wu, Shijia; Dai, Shaoliang; Gu, Huajie; Hao, Liling; Ye, Hua; Wang, Zhouping
Abstract : Food safety is a global health objective, and foodborne diseases represent a major crisis in health. Aptasensors have substantially been exploited for the detection of food contaminants. Abstract : Food safety is a global health objective, and foodborne diseases represent a major crisis in health. Techniques that are simple and suitable for fast screening to detect and identify pathogenic factors in the food chain are vital to ensure food safety. At present, a variety of analytical methods have been reported for the detection of pathogenic agents. Whereas the sensitivity of detection and quantification are still important challenges, we expect major advances from new assay formats and synthetic bio-recognition elements, such as aptamers. Owing to the specific folding capability of aptamers in the presence of an analyte, aptasensors have substantially and successfully been exploited for the detection of a wide range of small and large molecules ( e.g., toxins, antibiotics, heavy metals, bacteria, viruses) at very low concentrations. Here, we review the use of aptasensors for the development of highly sensitive and affordable detection tools for food analysis.